Building stress resistance: innovative pedagogical interventions for higher education students in war contexts - Кривошей, Кирило Юрійович; Kryvoshei, K. Yu. (Одеса : Гельветика, 2025)
The purpose of this article is to explore pedagogical approaches to enhancing the stress resistance of higher education students in the context of war. It is noted that modern students face significant psychological challenges caused by uncertainty, changes in learning formats, security threats, and forced migration. Therefore, the issue of their stress resistance and adaptation is highly relevant. The research methodology is based on the principles of systematization, development, and the psycho-pedagogical approach, as well as the use of methods such as scientific literature analysis, empirical research, and comparative analysis of educational practices. The scientific novelty lies in identifying pedagogical conditions that contribute to increasing students’ stress resistance, including the creation of a safe and predictable educational environment, optimization of academic workload, implementation of active learning methods, and the introduction of psychoeducational programs. Special attention is given to the role of educators in fostering a supportive learning environment and applying an individualized approach to students, which enhances their adaptation. Additionally, the importance of integrating, emotional self-regulation methods, and psychosocial support into the educational process is emphasized, as these contribute to students’ adaptation to crisis conditions. Conclusions. Chronic stress caused by war-related factors negatively impacts students’ cognitive processes, emotional state, and academic performance. The development of constructive coping skills, critical thinking, and social interaction strengthens stress resistance. It has been determined that a systematic approach to developing stress resistance in the educational environment is an urgent necessity. The implementation of innovative teaching methods, psychosocial support programs, and the promotion of a culture of mutual assistance will enable students to maintain emotional stability and study effectively, even in challenging conditions.

Мета статті полягає в дослідженні педагогічних підходів до підвищення стресостійкості здобувачів вищої освіти в умовах війни. Зазначається, що сучасні студенти стикаються зі значними психологічними викликами, зумовленими невизначеністю, змінами у форматах навчання, загрозами безпеці й вимушеною міграцією. Тож нині надзвичайно актуальним є питання стресостійкості та адаптації здобувачів вищої освіти. Методологія дослідження ґрунтується на принципах системності, розвитку, психолого-педагогічного підходу, а також на використанні методів аналізу наукової літератури, емпіричних досліджень та порівняльного аналізу освітніх практик. Наукова новизна полягає у визначенні педагогічних умов, що сприяють підвищенню стресостійкості здобувачів вищої освіти, зокрема: формування безпечного й передбачуваного освітнього середовища, оптимізація навчального навантаження, застосування активних методів навчання та впровадження психоосвітніх програм. Особливу увагу приділено ролі викладачів у створенні підтримувального освітнього середовища та використанні індивідуального підходу до студентів, що дозволяє ефективніше впливати на їх адаптацію. Також акцентовано увагу на важливості інтеграції в освітній процес методів емоційної саморегуляції та психосоціальної підтримки, що сприяє адаптації здобувачів до кризових умов. Висновки. Хронічний стрес, спричинений факторами війни, негативно впливає на когнітивні процеси, емоційний стан і рівень академічної успішності здобувачів вищої освіти. Розвиток навичок конструктивного копінгу, критичного мислення та соціальної взаємодії сприяє зміцненню психологічної стійкості. Визначено, що системний підхід до розвитку стресостійкості в освітньому середовищі є нагальною потребою сучасності. Впровадження інноваційних методів навчання, програм психосоціальної підтримки та розвиток культури взаємодопомоги дозволить здобувачам вищої освіти зберігати емоційну рівновагу та ефективно навчатися навіть у складних умовах.
Формування стресостійкості: інноваційні педагогічні підходи до здобувачів вищої освіти в умовах війни
Keywords: SOCIAL SCIENCES::Social sciences::Psychology; SOCIAL SCIENCES::Social sciences::Education; MEDICINE::Physiology and pharmacology::Physiology; stress resistance; resilience; higher education students; psychoeducation; pedagogical conditions; coping strategies; emotional self-regulation; psychosocial support; active learning methods; war; стресостійкість; резильєнтність; здобувачі вищої освіти; психоедукація; педагогічні умови; копінг-стратегії; емоційна саморегуляція; психосоціальна підтримка; активні методи навчання; війна